Reliability and diagnostic performance of smartphone colposcopy - Aydin, Serdar; GÖKMEN KARASU, AYŞE FİLİZ; GÖKMEN KARASU, AYŞE FİLİZ; Marasli, Mustafa; Bademler, Neslihan; KIRAN, Gürkan; KIRAN, GÜRKAN; DURAL, HANİFE RANA; DURAL, HANİFE RANA (My University, 2021)
Objective To evaluate the interobserver and intraobserver reliability of smartphone colposcopy (SPC) versus conventional colposcopy and to determine diagnostic performance.